2006
DOI: 10.1038/sj.jid.5700170
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Classical MAP Kinase Pathway Signalling in Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is a highly metastatic skin tumor. To assess the relevance of the Ras/Raf/MEK/MAP kinase pathway, we analyzed for activating B-Raf mutations and we elucidated the presence of the Raf Kinase Inhibitor Protein (RKIP) and extracellular signal-regulated kinase (ERK) as well as the phosphorylation status of ERK. All MCC samples were negative for the B-Raf(V600E) mutation. Remarkably, RKIP, which was shown to interfere with the activation of MEK by Raf, was highly expressed in primary as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 41 publications
1
49
1
1
Order By: Relevance
“…Recently, Swick et al determined that although eight of nine MCC tumors were positive for c-kit by immunohistochemical staining, no activating mutations were present in the four exons commonly found to have mutations in this gene [28]. Similarily, the analysis of MCC samples did not reveal presence of any activating B-Raf mutations [29,30]. Moreover, immunohistochemical studies revealed that despite high proliferation indices and existing expression of ERK, the ERK protein generally occurs in the non-phosphorylated form and is thus inactive [29].…”
Section: Pathogenesismentioning
confidence: 81%
“…Recently, Swick et al determined that although eight of nine MCC tumors were positive for c-kit by immunohistochemical staining, no activating mutations were present in the four exons commonly found to have mutations in this gene [28]. Similarily, the analysis of MCC samples did not reveal presence of any activating B-Raf mutations [29,30]. Moreover, immunohistochemical studies revealed that despite high proliferation indices and existing expression of ERK, the ERK protein generally occurs in the non-phosphorylated form and is thus inactive [29].…”
Section: Pathogenesismentioning
confidence: 81%
“…The classical MAP kinase signaling pathway was also examined in this skin carcinoma, and found to be not necessarily important, as there were no activating mutations in the B-Raf gene. 31 In this study, we evaluated the expression and mutational status of receptor tyrosine kinases, KIT and PDGFRA, in 32 cases of Merkel cell carcinoma. Expression of KIT was observed in 17 of 32 cases (53%).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Nevertheless, all three MAPK pathways seem to be involved in carcinogenesis and recent evidence suggests that P38l, one of the four P38 isoforms (P38a, P38b, P38k, and P38l), 36 is instrumental in malignant transformation linked to K-ras mutations. In a study of Merkel cell carcinoma, the ERK pathway was completely inactive in 42 of 44 cases, 37 but no information on the P38 pathway was provided. In the present study, there was immunopositivity for phosphorylated P38 in 26 of 31 cases of Merkel cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%